Circulating nucleic acids as diagnostic biomarker of cancer diseases (Experimental biology, 2018)
In the last decade, one of the most important trends of modern science is the search of the biomarkers, which would have high sensitivity and specificity for non-invasive diagnostics of cancer diseases. Immunological methods are not a well established practice in cancer diagnostics because of low specificity of currently used tumor markers.The study of free - circulating nucleic acids in plasma and serum of cancer patients represents a promising direction of modern molecular diagnostics.Free - circulating nucleic acids include DNA, RNA, microRNA, viral DNA / RNA and mitochondrial DNA. In this case, free-circulating nucleic acids can be present both in the free form and in the supramolecular nucleoprotein complexes.However, many aspects related to the biogenesis of free-circulating nucleic acids, as well as their role in the mechanism of carcinogenesis, are still not clear.This review focuses on the biological properties of free - circulating nucleic acids, biogenesis, their role in the pathogenesis of cancer and the possibility of using free - circulating nucleic acids as biomarkers in the diagnosis of cancer.Key words: free circulating nucleic acids, free circulating DNA, microRNA, mitochondrial DNA, cancer, biomarkers.